(untitled) (Wallingford, UK, 1994)
The book contains reports of a series of worshops on specialist topics - trapping, application of inert dusts, extension and small-scale and farm storage, standards, expert systems, and appropriate storage
Keywords: Food storage pests,Food; Control,Congresses,Storage,Congresses